Handbook of Qurʾānic Hermeneutics. Vol. 3: Qurʾānic Hermeneutics from the 13th to the 19th Century - Tamer, Georges (De Gruyter, 2025)
This project presents the hermeneutical approaches to the Qur'an of the most prominent Qur'anic scholars in Islamic intellectual history. Not only scholars who wrote commentaries on the Qur'an in the narrow sense of the word (tafasir) are to be presented, but also those who dealt hermeneutically with the Qur'an in various ways. The Handbook of Qur'anic Hermeneutics is the first book that discusses all the hermeneutical fields of the Qur'an. It will be published in seven volumes. • First handbook on Qur'anic Hermeneutics • Written by over 130 international researchers • Provides an overview in the diverse and intense discussed field.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Hermeneutics; Islamic studies; Qur'an; Religious studies